(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Infectious peritonitis in decompensated cirrhotic patients with ascites results in high morbidity and mortality. While spontaneous bacterial peritonitis and peritonitis secondary to perforation of hollow viscera have been well discussed and present well-defined diagnostic and treatment strategies, peritonitis secondary to violation of the peritoneal cavity, has been poorly studied. Objectives: Identify and describe a group of cirrhotic patients with secondary peritonitis associated with violation of the peritoneal cavity. Methods: A retrospective observational study conducted on cirrhotic patients with ascites, with a polymorphonuclear count greater than 250 cells/mm3 in the ascitic fluid and a record of abdominal or pelvic wall wound, with ascitic fluid leakage for more than 24 hours, preceding the diagnosis of peritonitis. Results: Secondary peritonitis associated with peritoneal cavity violation was observed in 4.25% (10 cases/235 admissions) of the total admissions and 24.4% of the total peritonitis (10 cases out of 45 cases). Most wounds that led to peritonitis were related to complications from umbilical hernias (07/10). The treatment proved to be challenging, with the need to change antibiotic therapy in 70% of the cases. Conclusion: Secondary peritonitis associated with violation of the peritoneal cavity corresponded to a quarter of the cases of peritonitis in cirrhotic patients with ascites treated by a referral service. Further studies are needed to help improve diagnostic, treatment and possible prophylaxis strategies.